Cognitive bias in professional hand hygiene and feedback: a national online-survey on overconfidence in Germany - Bushuven, Stefan; Weidenbusch, Marc; Mohr, Stefan; Delis, Achilles; Fischer, Martin R.; Juenger, Jana; Dettenkofer, Markus (Infection control and hospital epidemiology, 2019)
To evaluate learning motivation barriers in infection control and feedback competences, we conducted a national online survey in Germany. Among 767 healthcare workers, overconfidence effects could be detected independent from age, gender, profession, education, and hospital-size. The identified effects may impair learning motivation relevant for supervisors and educators in infection control.
Gesehen am 13.12.2019